EFEKTIVITAS BAKTERI ASAM LAKTAT NIRA LONTAR DALAM SILASE JERAMI PADI - Foeh, Nancy; Detha, Annytha; Ndaong, Nemay; Datta, Frans Umbu; Ludji Pau, Putri (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2020)
One of feed preservation method in the form of an airtight silo (anaerobic) is silage. The addition of Lactic Acid Bacteria in rice straw can increase the quality and quantity of silage products. The purpose of this research is to determine whether the lactic acid bacteria isolated from palm sap can be used as a starter in making silage and to determine the level of damage and pH of jermai silage up to day 14. The stages of this method include: making probiotics, making silage with treatment: (P0: EM4; P1: BAL 50ml; P2: BAL 75ml; P3: BAL 100ml; P4: BAL 125ml; P5: BAL 150ml; P6: BAL 175ml). The results showed that lactic acid bacteria from palm sap can be used as a starter in rice straw, at P1 with the addition of 50 ml lactic acid bacteria showed better silage results when compared to other treatments, which was characterized by light brown silage quality ( golden yellow), soft texture, sour smell, 4.54% silage presentation damage and pH 5.